Improving the Ability of Understanding Mathematical Concepts through Digital-based Comics for Elementary School Students - Rida Fironika Kusumadewi; Amos Neolaka; Mahmuddin Yasin (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study was intended to improve the ability in understanding mathematical concepts through digital-based comics. The population in this study were the fifth grade elementary school students in the Genuksari area, Semarang, Indonesia, totaling 120 students, with sample of 58 students. The instrument used in this study was a test of the ability to understand mathematical concepts. Meanwhile, the research data were analyzed using different test (t-test) and normalized gain test. The results showed that the t test results showed t-count = 39.74 > t-table = 1.98 at the significance level Î± = 0.05. This means that the use of digital-based comic teaching materials is better than conventional books. Meanwhile, the results of the n-gain test showed that the pretest value was 61.17 and the posttest value was 90.96 with an average value of 0.73 increase in the high category. So, it can be concluded that the teaching materials developed could increase students' ability to understand mathematical concepts. Therefore, the use of teaching materials digital-based comics is very effective and becomes an alternative in increasing the ability to understand mathematical concepts in elementary school students.Keywords: teaching materials, digital comics, ability to understand mathematical concepts.Â AbstrakPenelitian ini bertujuan untuk meningkatkan kemampuan pemahaman konsep matematika melalui komik berbasis digital. Populasi dalam penelitian ini adalah siswa kelas lima sekolah dasar di wilayah Genuksari, Semarang, Indonesia yang berjumlah 120 siswa, dengan sampel 58 siswa. Instrumen yang digunakan dalam penelitian ini berupa tes kemampuan pemahaman konsep matematika. Sementara itu, data hasil penelitian dianalisis menggunakan uji beda (t-tes) dan uji gain ternormalisasi. Hasil penelitian menunjukkan bahwa hasil uji t menunjukkan t-hitung = 39,74 > t-tabel = 1,98 pada taraf signifikansiÂ Î± = 0,05. Artinya penggunaan bahan ajar komik berbasis digital lebih baik dari buku konvensional. Sedangkan hasil uji n-gain diperoleh bahwa nilai pretest sebesar 61,17 dan nilai posttest sebesar 90,96 dengan nilai rata-rata peningkatan sebesar 0,73 dengan kategori tinggi. Sehingga dapat disimpulkan bahan ajar yang dikembangkan dapat meningkatkan kemampuan pemahaman konsep matematika siswa. Oleh karena itu, penggunaan bahan ajar komik berbasis digital sangat efektif dan menjadi alternatif dalam meningkatkan kemampuan pemahaman konsep matematika pada siswa sekolah dasar.Kata kunci: bahan ajar, komik digital, kemampuan pemahaman konsep matematika.